Material Contact and Environmental Effects on Vitamin A Fortified Vegetable Frying Oil - Wening, Sukmo; Andayani, Dewi Yuliyanti; Jayanti, Latifun; Christianti, Isti; Mulyono, Karyanto; Wassell, Paul (Department of Technology of Agricultural product (THP) Jambi University, 2020)
Observations about the impact of environmental parameters and time, on fortified vegetable oil, using typical commercial grade linear low density polyethylene (LLDPE) packaging during typical shelf-life conditions, are minimal. We tested the long-term (12 months) impact of temperature and illuminance (light: 100 to 150 lux and darkness <1 lux) on refined bleached deodorized palm olein (RBDPOL), fortified with vitamin A, and without antioxidant. Results showed degradation of fortified RBDPOL with 70 ppm vitamin A was approximately 19% at 18-22oC in Light, 18% at 18-22oC in Darkness, 38% at 32-33oC in light and 24% 32-33oC in darkness. A similar trend was observed at 45 ppm vitamin A. Exposure to both heat and light impacted vitamin A degradation, but was primarily attributed to prolonged exposure at elevated temperature, irrespective of the packaging material. This short study validates extensive research by Silalahi et al., (2017), doi:10.1111/ijfs.13462 on the impact of environmental effects of fortified vegetable frying oil, during extensive storage life periods.